FENOMENA CHILDFREE DALAM PERSPEKTIF NORMATIF SOSIOLOGIS - Putri, Rizky Silvia (Jurnal GeoCivic, 2024)
This article is the result of research on the Childfree Phenomenon which is an issue that is hotly discussed, especially on Indonesian social media. Childfree is an agreement made by a husband and wife not to have children during their marriage. This is a phenomenon that is quite controversial because in the cultural construction of Indonesian society, children are considered a gift and also one of the goals of marriage. More specifically, this article discusses what factors influence people to choose not to have children and how Islamic law views this phenomenon as well as the sociological impact on this phenomenon. To answer the problems that arise in this regard, this study uses a normative-sociological approach. that textually there is no textual verse which prohibits the choice of childfree. Having offspring is a recommendation in Islam is not an obligation. So that childfree does not include prohibited acts, because every married couple has the right to plan and manage their household life including having children. Nevertheless, it is important to note that in Islam children are seen as a gift that must be grateful for because children are a gift from God. So this is not in accordance with the principles of Maqasid As-Syariah in terms of protecting offspring (Hifdz an-Nasl).